أثر إضافة ماء الجفت بمستويات مختلفة من السعة الحقلية على بعض الخصائص الفيزيائية والهيدروديناميكية للتربة وعلى إنتاجيتها من محصول البطاطا Solanum Tuberosum.L)) (Latakia University Journal -Biological Sciences Series, 2017)
نفذ هذا البحث لدراسة أثر إضافة ماء الجفت بمستويات مختلفة من السعة الحقلية على بعض الخواص الفيزيائية والهيدروديناميكية لتربة طينية ثقيلة وعلى إنتاجيتها من محصول البطاطا. تبين إن الكثافة الظاهرية للتربة في الطبقة السطحية تنخفض بشكل معنوي بمقدار0.12غ/سم3 عند مستوى الإضافة 12.5% من السعة الحقلية مقارنة بالشاهد ولم يلاحظ فروق معنوية بين باقي مستويات الإضافة المطبقة, وفي العمق 20-40 سم فقد انخفضت الكثافة الظاهرية بمقدار0.08غ/سم3 عند مستوى الإضافة 25% من السعة الحقلية وبمقدار 0.17غ/سم3 في المعاملة 75% من السعة الحقلية مقارنة مع الشاهد. وزاد حجم المسامات الهوائية أكبر من10 ميكرون في العمق0-20سم بمقدار4.42% حجماً عند مستوى الإضافة 12.5% من السعة الحقلية وهذه المعاملة لم تختلف معنوياً عن باقي المعاملات, وفي العمق 20-40 سم زاد حجم المسامات الهوائية أكبر من 10ميكرون بمقدار 3.32%حجماً في المعاملة 50% مقارنة مع الشاهد. وزاد حجم المسامات التي تحوي الماء المتاح بمقدار 7.32% حجماً و 4.78% حجماً في المعاملتين 100% و75% من السعة الحقلية في العمقين 0-20 سم و 20-40 سم على التوالي, كما زادت قيمة معامل التوصيل الهيدروليكي المشبع بمقدار 0.35م/يوم و0.39 م/يوم في كل من العمقين (0-20)سم و(20.40)سم على التوالي في المعاملة 50% من السعة الحقلية.أما بالنسبة لثباتية الوحدات البنائية فلقد زادت مع زيادة مستويات الإضافة لتصل قيمة متوسط تغير القطر MD إلى أفضل قيمة لها 2.39 ملم عند المعاملة 50% من السعة الحقلية.وانعكس هذا التحسن في خواص التربة الفيزيائية على زيادة الإنتاج حيث بينت علاقة الارتباط أن أفضل مستوى للإضافة هو 55% من السعة الحقلية حيث كانت الزيادة بمقدار 31.06% مقارنة مع الشاهد. وهذه الزيادة لم تختلف معنوياً عن نسبة الإضافة 18% لذلك يمكن الاكتفاء بإضافة ماء جفت 18% من السعة الحقلية لهذا النوع من الترب .This research work was carried out to study the effect of adding Olive mill waste water to heavy clay soil at different levels of field capacity on some physical and hydrodynamic properties and its productivity of potato crop. It was noted that the bulk density of the surface soil reduced by 0.12 g / cm3 with the level 12.5% of field capacity compared to the control and no significant differences were observed between the rest of the applied levels, and in-depth 20-40 cm the bulk density decreased by 0.08 g / cm3at level 25% of field capacity and increased by 0.17 g / cm3in the treatment 75% of field capacity compared to the control .In depth 0-20 cm the volume of air pores increased larger than 10 microns about 4.42% by volume at the addition 12.5% of field capacity, and this treatment was not different significantly from the rest of the treatments, and in the depth of 20-40 cm The volume of air pores increased larger than 10 microns about 3.32% by volume in the treatment of 50% compared with the control. And the volume of the pores containing the available water increased about 7.32% by volume and 4.78% by volume, in the two treatments 100% and 75% of field capacity in the both depth 0-20 cm and 20-40 cm, respectively, also the value of the saturated hydraulic conductivity coefficient increased by 0.35 m/day and 0.39 m/day in the depth (0-20 cm) and (20-40 cm), respectively in treatment 50% of field capacity. It was also noted The stability of the structural units increased with increasing the addition rates that the change in the average secondary particle diameter MD reach to the best value 2.39 mm in the transaction 50% of the field capacity. This improvement in the soil physical properties was reflected on the increase in production where the correlation showed that the best level of addition is 55% of field capacity , Where the increase was about 31.06% compared with the control, and this increase is not different significantly from the addition 18% , so we can simply add olive mill waste water by 18% of field capacity for this type of soils.